The heart of change : - Kotter, John P. (Harvard Business Review Press, 2012)
The Heart of Change is your guide to helping people think and feel differently in order to meet your shared goals. According to bestselling author and renowned leadership expert John Kotter and coauthor Dan Cohen, this focus on connecting with people’s emotions is what will spark the behavior change and actions that lead to success. Now freshly designed, The Heart of Change is the engaging and essential complement to Kotter’s worldwide bestseller Leading Change.